STUDENTS' DISCOURSE ON IMMIGRATION ATTITUDES AND IDEOLOGICAL VALUES: A CRITICAL VIEW - Lopez Maestre, Maria D.; Scheu Lottgen, Dagmar (International Journal of English Studies, 2003)
Following an approach based on Critical Discourse Analysis and Discursive Psychology, in this paper we study the academic discourse of a group of students who were asked to express their ideas on immigration. In particular, we explore the discourse on immigration of a group of students of English Philology at the University of Murcia during the academic year 2001-2002. It is our aim to examine how attitudes are constructed around the topic of immigration, how these attitudes are discursively expressed (that is, how attitudes are constructed through their discourse practices), and what effects this type of discourse has on the other-representation of immigrants. A significant finding of the article has been the unravelling of how ideas uncounsciously assumed to be "politically correct", in fact cover highly racist and xenophobic attitudes to the phenomenon of immigration. Our paper shows how xenophobic attitudes still have not been overcome but are more than ever present in the discourse of the students who took part in the research conducted.